DISTRIBUIÇÃO POTENCIAL DO CASCUDO-CHINELO, Loricariichthys platymetopon (ISBRÜCKER & NIJSSEN, 1979), NA BACIA DO PRATA - ESTEVO, Andrielly Pimentel; SOUZA, Beatriz Cristina de Paula; BAILLY, Dayani; DELCONTE, José Hilário; RÉ, Reginaldo; BATISTA-SILVA, Valéria Flávia (ANAIS DO ENIC, 2024)
-